Die ring: in diens van onderlinge sorg - Celliers, A. (Acta Theologica, 2011)
Congregations of the Dutch Reformed Church in South Africa are facing various challenges which they cannot meet on their own. The classis or presbytery was born in the sixteenth century when reformed congregations also went through very difficult times. Its aim was to help congregations fulfil their needs. Neighbouring congregations that are close enough to understand each other’s needs and able to meet as often as needed, constitute this governing body. It has its roots in the sense of unity and concern that existed between the congregations of the first century. Throughout the history of the classis in the Dutch Reformed Church in South Africa, this same sense of unity and concern about the welfare of the congregations constituted the presbytery. Today it is still an integral part of the church’s organization and can help congregations to fulfil their God-given calling in their own context.